Inovasi Instrumen Penilaian Mahârah al-Kitâbah Berbasis HOTS pada Buku Teks Bahasa Arab - Eldara, Dian Soraya; Baroroh, R. Umi (Arabi : Journal of Arabic Studies, 2025)
This study aims to develop an innovative maharah al-kitabah assessment instrument based on Higher Order Thinking Skills (HOTS) in the ninth-grade Arabic textbook published by the Indonesian Ministry of Religious Affairs. The issue addressed in this study is the limited number of questions measuring HOTS in the existing textbook, resulting in a learning process that primarily focuses on basic skills such as remembering and understanding. This study employs the 4-D development model, which includes definition, design, and development. The research subjects are maharah al-kitabah questions found in the ninth-grade Arabic textbook. The findings indicate that most questions in the textbook emphasize Lower Order Thinking Skills (LOTS), with only a few assessing higher-order skills such as analysis, evaluation, and creation. Based on these findings, this study proposes the development of HOTS-based questions that encourage students to think more critically and creatively, such as questions that assess text analysis, evaluation, and creative writing skills.